[PP.LB03.10] THE METABOLIC SYNDROME IN APPARENTLY HEALTHY ADOLESCENTS FROM AN URBAN POPULATION IN GUAYAQUIL, ECUADOR. (September 2016) - Palacios, F. Aguirre; Coca, A.; Paredes, M.; Aguirre, M.
Abstract : Objective: To determine the prevalence of the metabolic syndrome (MS) and the existence of vascular inflammation in adolescents of both gender, aged 12–14 years. Design and method: 396 apparently healthy students where included in a prospective and descriptive cross-sectional survey. Informed consent of their parents was required, and anthropometric measurements including BP, BMI, and blood tests were obtained to analyze MS-related parameters, and to study vascular inflammation. Percentiles of the different parameters where used, and MS was defined according to NCEP ATP III criteria. Results: The prevalence of MS was 12.6%; obesity 1.8%, pre-HT (>P90) 7.1%, and HT 13.7%. In patients with the MS the OR (95%CI) for high Triglycerides was 2.3 (95%CI 1.9 to 2.7), HOMA 1.9 (95%CI 1.6–2.4), low HDL 1.8 (95%CI 1.5–2.1), insulin 1.53 (95%CI 1.4- 1.6), interleukin-6 1.8 (95%CI 1.1 to 2.7) and CRP-hs 1.1 (95%CI 0.8–1.5). Vigorous exercise> 20 minutes 3 times per week showed an inverse correlation with the BMI, but not the usual twice-a-week physical exercise performed at the school. Conclusions: The MS correlated with BMI, inflammation and insulin resistance, and was associated with pre-hypertension and true hypertension compared to non-obese subjects. The adoption of healthy diets and vigorous exercise in adolescents is crucial to prevent cardiovascular disease in the older age. Figure. No caption available.